A Decisional Study of Criminal Liability of Road-Based Mass Transportation Drivers in Special Bus Lanes - Wardana Kusuma, Wisnu; Pardomuan Sibuea, Hotma; Dewi Sartika Saimima, Ika; Tri Indra Setiawan, Guntur (Universitas Medan Area, 2024)
This research aims to make a decision study of criminal liability of road-based mass transport drivers in special bus lanes. The research method used is normative juridical. This result of the research shows that drivers of road-based mass transportation buses who enter special bus lanes should not be punished if someone breaks through the special bus lane which results in an accident and the victim dies. This is based on legal experience, namely on court decisions based on articles relating to road user negligence. The decision made by the judge in the case of death due to someone breaking into a special bus lane exampale in case Decision Number 1086 K/PID/2016 and others is not commensurate with the driver's fault because the incident occurred due to the fault of the perpetrator or the victim themselves. This decision also cannot apply to mass transit bus drivers because basically it is necessary to pay more in-depth attention to causal factors, as well as Victim Precipitation conditions which are the initial causes of accidents in special bus lanes. This research is a form of proposed change in Law No. 22 of 2009 concerning Traffic and Road Transportation.